2013
DOI: 10.1002/acr.21820
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence in patients with autoimmune rheumatic diseases: A nationwide population‐based study in Taiwan

Abstract: Objective. The purpose of this study was to determine the prevalence, incidence, and mortality rates of autoimmune rheumatic diseases (ARDs) by using a population-based database. Methods. We used the longitudinal health insurance database (comprising 1,000,000 beneficiaries) of the Taiwan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 47 publications
6
90
4
2
Order By: Relevance
“…Of six studies reporting IR, three were from Taiwan 13 19 33. The subgroup meta-analysis stratified by country showed that IR of pSS in Taiwan was 6.57 (95% CI 6.37 to 6.76) and had significant heterogeneity (p<0.001, I 2 =99.25%).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Of six studies reporting IR, three were from Taiwan 13 19 33. The subgroup meta-analysis stratified by country showed that IR of pSS in Taiwan was 6.57 (95% CI 6.37 to 6.76) and had significant heterogeneity (p<0.001, I 2 =99.25%).…”
Section: Resultsmentioning
confidence: 97%
“…A total of 1808 articles were excluded based on screening of abstracts or titles, leaving 72 articles for the full-text review and assessment for eligibility. Fifty-one of these articles were excluded after retrieving the full-text articles (figure 1), leaving 21 eligible studies for inclusion in the meta-analysis 13–33. The agreement between reviewers for the eligibility of articles was 100%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical symptoms involve recurrent flares of acute arthritis, chronic arthropathy, tophi, uric acid urolithiasis, and renal impairment [1,2]. The affected joints the Taiwan general population from 2000 to 2008, the prevalence of rheumatoid arthritis was 52.4 per 100,000 persons, and the incidence was 17.3 per 100,000 person-years [8]. A multicenter study of UK general practices showed a 3-fold rise in gout occurrence between the 1970s and the 1990s (from 0.03 to 0.095%) [9] and a 1.4% rise from 2000 to 2005 compared to IMS databases from Germany and UK [10].…”
Section: Introductionmentioning
confidence: 99%